MISOGYNY IN THE TRAIT: VIOLENCE AGAINST WOMEN AS THE THEMATIC PRETEXT IN EDITORIAL CARTOONS - Volpato, Alana N. [UNESP]; Damiao, Nayara A.; Miani, Rozinaldo A. (Univ Federal Paraiba, 2018)
This article discusses the use of violence against women as a thematic pretext used as an visual argument in the production of editorial cartoons. We understand that editorial cartoons consist of a mode of graphic humor, produced by the human trait, of dissertative nature. The editorial cartoon, imbued with political and social criticism, is constructed by portraying a certain point of view on a historical fact through visual means. Produced in the patriarchal society, editorial cartoons can reproduce the relations of domination and exploitation to which women are subjected. Through the methodology of analysis of the cartoon discourse, we analyze the presence of women in editorial cartoons that discuss subjects like politics, economy and society, emphasizing the use of violence against the woman like a thematic pretext to construct the criticism in the editorial cartoon, which contributes to the maintenance of stereotypes and the oppressive condition imposed on women
Keywords: Violence against women; Patriarchy; Editorial cartoon; Graphic humor